2014
DOI: 10.1093/hmg/ddu335
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of KCNH7 p.Arg394His and bipolar spectrum disorder

Abstract: We conducted blinded psychiatric assessments of 26 Amish subjects (52 ± 11 years) from four families with prevalent bipolar spectrum disorder, identified 10 potentially pathogenic alleles by exome sequencing, tested association of these alleles with clinical diagnoses in the larger Amish Study of Major Affective Disorder (ASMAD) cohort, and studied mutant potassium channels in neurons. Fourteen of 26 Amish had bipolar spectrum disorder. The only candidate allele shared among them was rs78247304, a non-synonymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…We found an elevated burden of risk variants in nicotinic acetylcholine receptors and CaM kinases. Others have reported variants in potassium channels and other gene sets (7,12). As larger sample sizes become available, it will be possible to conduct unbiased genome-wide analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found an elevated burden of risk variants in nicotinic acetylcholine receptors and CaM kinases. Others have reported variants in potassium channels and other gene sets (7,12). As larger sample sizes become available, it will be possible to conduct unbiased genome-wide analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that one or a few rare variants of large effect dramatically increase disease risk, resulting in an inheritance model resembling monogenic inheritance in a given family. However, four exomesequencing and whole-genome sequencing (WGS) studies of BD pedigrees have detected few, if any, plausible variants of large effect (6)(7)(8)(9). An alternative oligogenic model posits that different combinations of several uncommon or rare variants of moderate effect cluster in affected individuals and collectively cause disease.…”
mentioning
confidence: 99%
“…1013 Two family studies 12,13 of the Amish population found evidence for partial segregation of a number of variants but little convergence on a specific gene or a linkage location. Similar results were found by Collins et al, 10 who performed exome sequencing of a large pedigree without conclusively identifying variants of large effect, and by Cruceanu et al, 11 who studied 25 pedigrees with lithium-responsive BD and also found limited evidence for cosegregation at the level of variants or genes across families.…”
mentioning
confidence: 99%
“…This work was pioneered by Egeland and colleagues in the late 20 th century (Egeland et al 1989;Egeland1983). Ongoing studies are now being pursued by several groups (Yang et al 2009;Egeland et al 2012;Hou et al 2013;Ginns et al 2014;Strauss et al 2014;Georgi et al 2014;Kember et al 2015;Byrne et al 2015).…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Additional challenges arise from limited sample sizes and strong local population structures. For example, a recent study identified a missense mutation in the KCNH7 gene among Old Order Amish in Pennsylvania, some of whom suffered from bipolar or other mood disorders (Strauss et al 2014). In vitro functional studies seemed to demonstrate a clear impact of the variant on HERG3 channels, but small sample size and lack of matched controls hampered the establishment of a significant association with the disorder.…”
Section: Psychiatric Disordersmentioning
confidence: 99%